2001
DOI: 10.1007/s004670000526
|View full text |Cite
|
Sign up to set email alerts
|

End-stage renal disease in a patient with congenital lymphangiectasia and lymphedema

Abstract: Congenital lymphangiectasia with lymphedema is a disorder constituting the main defect in many different genetic syndromes. Herein we describe a 23-year-old male patient with congenital lymphangiectasia and severe lymphedema of the right leg, scrotum, and abdominal wall, who presented with end-stage renal disease, presumably due to cystic renal lymphangiectasia, and is undergoing chronic hemodialysis treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…At times there are cutaneous lymphangiectasias that erupt to the outside, causing leakage of lymph through the skin. The lymphangiectasias can also be present in the pleura, pericardium, thyroid gland [Scarcella et al, 2000], and kidney [Sombolos et al, 2001]. The latter distributions are especially rare, but solitary lymph vessel dysplasias at these loci have previously been described [Simonton et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At times there are cutaneous lymphangiectasias that erupt to the outside, causing leakage of lymph through the skin. The lymphangiectasias can also be present in the pleura, pericardium, thyroid gland [Scarcella et al, 2000], and kidney [Sombolos et al, 2001]. The latter distributions are especially rare, but solitary lymph vessel dysplasias at these loci have previously been described [Simonton et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…In the initial report [Hennekam et al, 1989], no abnormalities of the heart or blood vessels were found. Later reports have drawn attention to renal artery anomalies [Cormier‐Daire et al, 1995; Sombolos et al, 2001], with attendant renovascular hypertension in one of these instances [Cormier‐Daire et al, 1995], winding of the aortic arch [case JS], congenital heart defects such as VSD [Angle and Hersch, 1997; Scarcella et al, 2000; case RB] and atrial septal defect [Rockson et al, 1999; Rosser et al, 2000], and intracerebral infarctions [Huppke et al, 2000]. It is possible that the intracerebral cysts present in two cases [cases DW and JS] also have a vascular origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This autosomal recessive disorder first described by Hennekam et al [1989] includes intestinal lymphangiectasia with protein‐losing enteropathy, craniofacial dysmorphy, heart and genitourinary malformations, skeletal defects, mental retardation and seizures [Van Balkom et al, 2002]. In this context it is remarkable that in Hennekam syndrome lymphangiectasia has been rarely described in different organs such as pleura, pericardium, thyroid gland, and kidneys [Scarcella et al, 2000; Sombolos et al, 2001]. Therefore, it is conceivable that Hennekam syndrome and the cases reported by Njolstad, Jacquemont and us may be variable manifestations of the same entity.…”
Section: To the Editormentioning
confidence: 99%